Attitude Towards Ageing Anxiety Among Different Age Cohorts in Anambra State, Nigeria - Maduekwe, Theresa Chika; Ekenedo, Golda O. (European Scientific Journal, ESJ, 2018)
The study was aimed at investigating the attitude towards ageing anxiety among different age cohorts in Anambra State. Three research questions and two hypotheses guided the study. A cross sectional survey design was adopted for the study. The variables that influence the attitude were ascertained in line with the objectives of the study. The accessible population for the study consisted of all the different age cohorts from ten randomly drawn Local Government Areas in the state. The sample for the study consisted of 736 different age cohorts selected from the five education zones in the state. Multi-stage sampling procedure comprising cluster, simple random sampling, proportionate sampling and stratified random sampling were used in selecting the LGAs, towns and respondents. A validated Ageing and Attitude Scale Questionnaire (AASQ) designed by the researchers was used for data collection. The data were analyzed using frequencies and percentages as well as the chi-square. The hypotheses were tested at 0.05 level of significance using computer-based epidemiological Information (Ep/Info) version 6.1 software. The findings revealed negative attitude towards ageing anxiety among the different age cohorts. Gender of the subjects significantly influenced their ageing anxiety whereas ages of the subjects had no significant influence on their ageing anxiety. It was concluded that ageing education intervention is needed to bring about a positive change in attitude towards ageing anxiety.